Countering a Future Crisis of Accountants with Decreasing Credibility: the Influence of Ethical Education and Religiosity on Ethical Perceptions of Accrual, Real Activity and Tunneling Manipulation - Sari, Ratna Candra; Sari, Annisa Ratna; Aisyah, Mimin Nur; Arifin, Azizah Hasna' (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2021)
Purpose: This study is intended to: First, examine the effectiveness of ethics education to instill core ethical values in students; Second, test the differences between students’ ethical perceptions in religious and public universities; Third, examine the effects of individual’s ethical ideology on ethical perceptions.Method: Questionnaire was used to collect data and SEM PLS was used to test the hypotheses. A total of 215 undergraduate students from public and private university have taken part in this study.Findings: The study show that business ethics education does not influence ethical perceptions. However, there is a significant difference in students’ ethical perceptions between the public university and religious-based universities. Furthermore, result shows that individuals’ ethical ideology has an impact on ethical perceptions.Novelty: This study differs from previous research because most of the previous studies focused on the ethical judgments of the accruals and real activity manipulation methods but have limited ethical considerations regarding tunneling. Meanwhile, the business group structure and low legal enforcement have led to many cases of tunneling in Indonesia.